Cold Chain Logistics at Agriculture Operations in Vietnam - Truong, Khanh Nhat (2024)
The Bachelor’s thesis aims to propose insights to enhance the cold chain logistics at Agriculture Operations in Vietnam. The analysis of the Five Performance Objectives of Operations Management. This perspective permits the identification of challenges maintaining product integrity during the process. The essay contributes to additional insights on the understanding of the Cold Chain Logistics at Agriculture Operations by describing the specifics of Five Performance Objectives of Operations Management. The research reviews Overall, the findings show that the operation of the Gemadept company, which contributes to a practical understanding of their operation and proposals for their enhancement.